General Cause. The Red Domination in Spain: The exhibition of the image as political propaganda - Jiménez Barroso, María Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study aims to analyze the set of photographs included in the work Causa General. The red domination in Spain. Advance of the information instructed by the Public Ministry, published by the Ministry of Justice in December 1943, to find out its possible influence on the construction of the collective imaginary. From this work three concepts emerge that will be the images associated with that period: anarchy, persecution of the church and the link between the republican government and Russia. As well as the transversal idea of the inevitability of the coup.